The Essential Dickens: A Critical Observation - Ajitesh Singh (The Creative Launcher, 2018)
This article intends to delineate the meaning of Dickens in the contemporary world and for contemporary novelist. As the aspiring novelist would look at Dickens, as well as the art of fiction, his/her mind is likely to see that Dickens’ art is imbued with a sense of comprehensiveness. David Cecil has noted that for from being a specialist Dickens has almost every kind of fictional technique and content in his work. This is in fine contrast to most novelist of the 20th century and later, who tend to be specialists – choosing to write only one or the kinds of fiction. Thus there are mystery novels, historical novels, social novels, psychological novels, magical realism novels, autobiographical novels, crime novels and so on. Dickens’ vision incorporated all these and more because of which he had something for everyone. He was thoroughly aware of the heterogeneity of the Victorian public and therefore his novels were aimed at including as many categories of readers as possible. He could provide a rather complete picture of life and thus a complete kind of satisfaction for the reader. New Historicists believe that Dickens’s novels “have functioned and can still function as interactive social discourse.”